2017
DOI: 10.1002/bin.1474
|View full text |Cite
|
Sign up to set email alerts
|

Effects of response independent delivery of preferred items and the high‐probability instructional sequence on compliance

Abstract: The use of the high-probability (high-p) instructional sequence to increase compliance, which includes issuing a series of instructions with which a participant is likely to comply immediately before issuing a low-probability instruction, has received mixed support in the literature. Previous research has suggested that the delivery of response independent reinforcement may be as effective to increase compliance, at least for some types of instructions. In this study, we examined the effects of response indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Given that multiple studies have shown positive effects of the HPS on feeding responses in children with autism and FS, our failure to replicate these effects was surprising. Yet, the current findings are consistent with prior failures to replicate the positive effects of the HPS in children with compliance problems (e.g., Lipschultz, Wilder, & Enderli, 2017; Rortvedt & Miltenberger, 1994). The current findings weaken the certainty of the evidence for HPS effects on feeding specifically, but do not invalidate the results of prior research.…”
Section: Discussionsupporting
confidence: 87%
“…Given that multiple studies have shown positive effects of the HPS on feeding responses in children with autism and FS, our failure to replicate these effects was surprising. Yet, the current findings are consistent with prior failures to replicate the positive effects of the HPS in children with compliance problems (e.g., Lipschultz, Wilder, & Enderli, 2017; Rortvedt & Miltenberger, 1994). The current findings weaken the certainty of the evidence for HPS effects on feeding specifically, but do not invalidate the results of prior research.…”
Section: Discussionsupporting
confidence: 87%
“…Despite the recent increase in research on the high‐p instructional sequence (c.f., Lipschultz & Wilder, ), the delivery of preferred stimuli may be more important than any high‐p instructional feature to increase compliance with a low‐p instruction. Previous research has found that contingent access to preferred edibles is often more effective than the high‐p sequence to improve compliance with a low‐p instruction (Lipschultz, Wilder, & Enderli, ). Given this, the relative utility of the high‐p sequence with contingent reinforcement may be unclear in comparison to directly reinforcing low‐p compliance (without a high‐p sequence).…”
Section: Discussionmentioning
confidence: 99%
“…In Experiment 2, longer durations of access to preferred leisure items produced larger increases in compliance. These data elaborate on the mixed findings from previous studies (Bullock & Normand, 2006;Lipschultz et al, 2017;Normand & Beaulieu, 2011). That is, the magnitude and the duration of access to the preferred item during pretrial delivery may moderate its effectiveness.…”
Section: Discussionmentioning
confidence: 54%
“…The authors noted that the one instruction for which the procedure was ineffective involved relinquishing access to a preferred game, and that continued access to the game may have been more valuable than access to the preferred edible item in the moment the low-p instruction was delivered. Lipschultz et al (2017) further evaluated a FT schedule to increase compliance in two young children. These researchers first implemented a FT 20-s schedule, followed by a FT 10-s schedule immediately before presenting a low-p instruction.…”
mentioning
confidence: 99%